CGRP receptor antagonist activity of olcegepant depends on the signalling pathway measured. (March 2018) - Walker, Christopher S; Raddant, Ann C; Woolley, Michael J; Russo, Andrew F; Hay, Debbie L
Background: Calcitonin gene-related peptide (CGRP) is a neuropeptide that acts in the trigeminovascular system and is believed to play an important role in migraine. CGRP activates two receptors that are both present in the trigeminovascular system; the CGRP receptor and the amylin 1 (AMY1 ) receptor. CGRP receptor antagonists, including olcegepant (BIBN4096BS) and telcagepant (MK-0974), can treat migraine. This study aimed to determine the effectiveness of these antagonists at blocking CGRP receptor signalling in trigeminal ganglia (TG) neurons and transfected CGRP and AMY1 receptors in Cos7 cells, to better understand their mechanism of action. Methods: CGRP stimulation of four intracellular signalling molecules relevant to pain (cAMP, CREB, p38 and ERK) were examined in rat TG neurons and compared to transfected CGRP and AMY1 receptors in Cos7 cells. Results: In TG neurons, olcegepant displayed signal-specific differences in antagonism of CGRP responses. This effect was also evident in transfected Cos7 cells, where olcegepant blocked CREB phosphorylation more potently than expected at the AMY1 receptor, suggesting that the affinity of this antagonist can be dependent on the signalling pathway activated. Conclusions: CGRP receptor antagonist activity appears to be assay-dependent. Thus, these molecules may not be as selective for the CGRP receptor as commonly reported.